Insidensi Bayi Berat Lahir Rendah pada Spektrum Plasenta Akreta di Rumah Sakit Dr Hasan Sadikin Bandung - Yuktiana Kharisma; Hasrayati Agustina; Sri Suryanti; Birgitta Maria Dewayani; Bethy Suryawati Hernowo (Jurnal Kesehatan Andalas, 2022)
Low birth weight (LBW) babies are closely related to infant morbidity, stunted growth and cognitive development, and chronic diseases. Placenta accreta spectrum (PAS) is a condition that complicates pregnancy and is closely related to low birth weight. Objectives: To determined the incidence of LBW in mothers with SPA at the hospital Dr. Hasan Sadikin Bandung. Methods: A descriptive observational study involving 71 cases of SPA in hospitals  Dr. Hasan Sadikin Bandung, period 2016-2020, which has met the inclusion and exclusion criteria. SPA cases were divided into three groups: placenta accreta, increta, and percreta. In each SPA group, the incidence of LBW was evaluated. Results: 46.5% (33/71 cases of PAS) had low birth weight, while 53.5% (38/71 cases of PAS) had normal birth weight babies. The placenta accreta and percreta groups were dominated by normal birth weight infants [(18/31 cases), (5/9 cases)], while the placenta increta group was dominated by low birth weight infants (16/31 cases). The LBW category is divided into Extremely Low Birth Weight (ELBW), Very Low Birth Weight (VLBW), and LBW. In placenta accreta, there were 2 ELBW and VLBW infants, and 9 LBW infants. In the placenta increta, there are 3 ELBW and VLBW, and 10 LBW. In the placenta percreta, there were 1 ELBW and 3 LBW, while VLBW was not found in the placenta percreta. Conclusion: The incidence of LBW is found in almost half the population of SPA cases in hospitals. DR. Hasan Sadikin in the 2016-2020 period.Keywords:  low birth weight, placenta accreta spectrum